Quest for the General Effect Size of Finance on Growth: A Large Meta-Analysis of Worldwide Studies - Ichiro Iwasaki; Evžen Kočenda (Center for Economic Studies and ifo Institute (CESifo), 2023)
We analyze diverse and heterogenous literature to grasp the general effect size of financial development on economic growth on a world scale. For that, we perform by far the largest available meta-analysis of the finance–growth nexus using 3561 estimates collected from 177 studies. Our meta-synthesis results show that large heterogeneity in empirical evidence is, in fact, driven by only a limited number of variables (moderators). By using advanced techniques, we also document the existence of the publication selection bias that is propagated in the literature in a nonlinear fashion. We account for uncertainty in moderator selection by employing model-averaging techniques. After adjusting for the publication bias, the results of our meta-regression provide evidence of a small but genuine positive effect of the financial development on growth that very mildly declines over time. Finance channeled via capital markets seems to be more beneficial for economic growth than that provided in the form of private credit. Our evidence goes against arguments about the damaging role of financial development and is in line with century-old theoretical foundations that favor the positive role of finance on economic growth.
Keywords: C12; D22; G21; G33; 330; financial development; economic growth; meta-analysis; publication selection bias